Novel oxindole derivatives and their biological activity - Strigácová, J; Hudecová, D; Mikulásová, M; Varecka, L; Lásiková, A; Végh, D (Folia microbiologica, 2001)
The antifungal activity of fourteen novel derivatives of oxindole with side chain was studied using representatives of toxinogenic, phytopathogenic and dermatophytic filamentous fungi. Derivatives with exocyclic C=C bond in position C-3 exhibited a higher antifungal activity compared with derivatives with an exocyclic C-C bond in the same position. The strongest antifungal effects were shown by 3-(-2-thienoylmethylidene)-indol-2(3H)-ones.
Keywords: Fusarium; Mutagenicity Tests; Microsporum; Indoles; Penicillium; testy genotoxicity; Botrytis; Aspergillus flavus; Antifungal Agents; Microbial Sensitivity Tests; Oxidation-Reduction; Antineoplastic Agents; Trichophyton; Rhizopus; protinádorové látky; indoly; oxidace-redukce; mikrobiální testy citlivosti; antifungální látky